Economic Recovery Strategy For Small Tourism Enterprises During Covid-19 Pandemic In Jayapura Municipality - Matani, Cornelia Desiana; Meak, Karl Karolus; Salle, Hesty Theresia (UNIVERSITAS PAKUAN, 2025)
The research objectives are to; (1) assess the impact of Covid-19 on tourism small and medium-scale enterprises and their resistance; (2) outline the government intervention supporting small and medium enterprises; (3) examine local government programs for small and medium enterprises economic recovery and provide recommendations (4) identify strategies to recover businesses. The method used was descriptive qualitative and a content analysis. This research focused on small and medium-scale enterprises (SMSE) in tourism site from Hamadi to Holtekamp beach, Jayapura Municipality.The identification of income from the nine SMSEs studied found that only three SMSEs experienced a significant impact from the Covid-19 pandemic. In addition, from the workforce aspect, five SMSEs experienced a reduction in workforce during the Covid-19 period. In terms of visitor trends, Six SMSEs encountered the impact of the pandemic. Regarding the government policy intervention, there were budgets allocated for the prevention of Covid-19 in the SMSE sector, namely, Unexpected Expenditures Budget as well as Grant Budget with total of Rp. 7,314,685,000 which was realized at only Rp. 3,078,448,925 or 42.09%. In addition, the SMSE business managers viewed that the designed policies, program and activities were not precise for them. This research proposes some strategies: (1) providing assistance to increase SMSE resistance during the pandemic; (2) encouraging collaboration between government and business actors to improve business innovation which will increase SMSE business capacity (3) maximizing the use of digital platforms. As this research only relied on the perspectives of business owners and on regulations as well as government financial report documents, it is suggested that further research using various empirical data can be conducted, hence the factors determining the economic recovery strategy among SMSE can be more persistent. This study contributed to identification of SMSE strategy to sustain the business during covid-19 in eastern part of Indonesia.